THE IMPACT ROLE OF USING DENTAL AMALGAM "SILVER" FILLINGS ON THE CHOLINERGIC AND ENDOGENOUS ADRENERGIC ACTIVITY - ZAHRAA S. AL-GARAWI; FALAH S. AL-FARTUSIE; HAIDAR J. AL-FATLAWI (International Journal of Pharma and Bio Sciences, 2015)
The effect of silver dental amalgam fillings on cholinergic activity was investigated through measurement of AChE activity using UV-Vis spectroscopy by Ellman modified method. Results demonstrated that the enzyme activity decreased significantly in students have 1-2 fillings more than that observed in subjects have 3-5 amalgam fillings which still under control values. For long time exposure to the fillings (4 years), the enzyme activity diminished annually among young undergraduate male students (18-25 years old) when compared with control subjects. In addition, salivary α-amylase activities in the first group (1-2 mercury fillings) were none significantly lower than control subjects. Furthermore, serum Hg concentrations in target subjects were considerably higher than those without fillings. In conclusion, according to the changes observed in AChE activity by time of exposure and higher concentration of Hg, it is proposed that: increasing duration and number of amalgam fillings might in fact be capable of decreasing cholinergic activity whereas only slightly changes in adrenergic activity.